Teaching the Subject «Intellectual Property» in Higher Education - Стороженко, Ольга Михайлівна; Німко, Ольга Борисівна (Educological discourse, 2014)
The problems of methodical maintenance for teaching the discipline «Intellectual property» during training of experts in the educational law concerning intellectual property rights protection in the education and sciences are discussed in the article.